The Influence of Body Mass Index, Q-angle and Tibiofemoral Alignment on the Clinical Deficits of Osteoarthritis of the Knee - Bello, A.I.; Danso, J.A.; Bonney, E.; Oppong-Yeboah, B. (Jacobs Journal of Physical Rehabilitation Medicine, 2015)
Background: The underlying determinants of clinical deficits of knee OA remain crucial during objective assessment, which is yet to receive the deserved attention in practice. Objective: The study determined the influence of BMI, Q-angle and Tibiofemoral alignment (TFA) on pain, stiffness and physical function of patients with knee OA. Methods: Patients diagnosed with knee OA were recruited at physiotherapy departments of three health care settings in Ghana. The BMI of participants was determined through the standard formula [weight (kg)/height (m) 2]. The measurement of Q-angle and TFA followed routine manual methods with the use of goniometer and tracing sheet. To quantify pain in tensity, joint stiffness and physical function of participants, the domains of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was employed. Spearman’s correlation coefficient was used to determine the relationships between variables at p<0.05. Results: Fifty-two (52) patients with knee OA (Mean age; 60.2±10.4years) participated in the study. They comprised 9 (17.3%) males and 43 (82.7%) females. Participants’ BMI and Q angle were significantly and positively correlated with their physical functioning (rho=0.368; p=0.007) and (rho=0.332; p=0.016) respectively on the domains of WOMAC. However, par ticipants’ self-reported pain and stiffness as assessed on WOMAC index were not significantly correlated with BMI, Q angle and clinical TFA. Conclusion: BMI and Q-angle could considerably influence the overall clinical deficits in patients with knee OA particularly the physical function, thus placing emphasis on routine assessment of these variables in the clinical practice.
Research Article
Keywords: BMI; Q angle; Tibiofemoral alignment; Osteoarthritis